The relationship between anthropometric index and primary dysmenorehea in female high school students - Mostafa Rad; Marzieh Torkamannejad Sabzevari; Sedigheh Rastaghi; Zahra Mohebbi Dehnavi (Wolters Kluwer Medknow Publications, 2018)
Introduction: Primary dysmenorrhea, painful menstruation without pelvic pathologic complications, is one of the most common problems in women's gynecology and is one of the main causes for women referring to the clinic. Overweight and obesity may play a role in the etiology of primary dysmenorrhea. As a result, this study was conducted to determine the association between primary dysmenorrhea and anthropometric indices in female high school Students. Methods: This descriptive, cross-sectional study was conducted on 200 high school female students with primary dysmenorrhea in 2017 in Sabzevar. Anthropometric indicators were considered by the students if they had entry criteria. Data analysis was done using SPSS software. Results: The results of data analysis showed that there was a significant difference between the presence of dysmenorrhea and anthropometric indices at height P = 0.05, waist circumference P = 0.03, waist circumference with height P = 0.01, height to waist circumference P = 0.01, thigh circumference to height P = 0.04, height to thigh circumference P = 0.04, waist circumference to hip circumference P = 0.04, hip circumference to hip circumference P = 0.05, and No significant relationship was found between the other indicators. Conclusion: Adherence to a balanced diet and proper lifestyle can prevent dysmenorrhea in adolescent girls.